2005
DOI: 10.1093/rheumatology/kei231
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of subacute low back pain: influence of patients' and rheumatologists' characteristics

Abstract: Back pain commonly persists 3 months later in patients with subacute low back pain. Patients and rheumatologists still have negative beliefs about back pain. Rheumatologists' beliefs influence their following guidelines on physical and occupational activities. National education programmes about low back pain are needed in France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
3
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 28 publications
4
54
3
3
Order By: Relevance
“…This finding is consistent with a previous work by Nyland and Grimmer [32] that also found an increased lifetime prevalence of LBP in physiotherapy students and a significantly increased risk for students once they completed first year. However, previous research has not found association between health care providers personal experience of back pain and both the level of fear-avoidance beliefs [10,11,33] and the HC-PAIRS score [16,17].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This finding is consistent with a previous work by Nyland and Grimmer [32] that also found an increased lifetime prevalence of LBP in physiotherapy students and a significantly increased risk for students once they completed first year. However, previous research has not found association between health care providers personal experience of back pain and both the level of fear-avoidance beliefs [10,11,33] and the HC-PAIRS score [16,17].…”
Section: Discussionmentioning
confidence: 86%
“…Although FABQ was originally designed to measure beliefs and attitudes in patients [20], it has also been used to measure these qualities in health care providers. Coudeyre [10] and Poiraudeau [11] showed in physicians (general practitioners and rheumatologists) that a high score in FABQ was associated with a higher rate of recommendations of bed rest, sick leave and less advice to maintain maximum bearable physical activities for chronic LBP. In our study, correlations between the FABQ-W and FABQ-Phys and the HC-PAIRS were moderate, suggesting that our hypothesis were met and that convergent validity was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of, or potentially because of unclear decision contexts, patients as well as HCPs form perceptions relating to the available options based on additional factors not relating to clinical evidence. Studies have shown that HCPs treat patients differently in accordance with their own perception of diagnosis and that HCPs are heavily guided by their beliefs about back pain in general and about the individual patient, in their treatment recommendations Poiraudeau et al, 2006;Houben et al, 2005Houben et al, , 2004Corbett et al, 2009;Pincus et al, 2007;Balagué et al, 2012;Bishop et al, 2008; In line with the above, this paper argues that, possibly particularly in scenarios where clinical evidence is limited or not clear cut, perceptions that the patient forms, either through past experience or through discussion with other patients and/or medical experts, will play a major role in shaping his or her decisions. Researchers outside of health economics have increasingly recognised that a large share of this heterogeneity could be linked to underlying values, perceptions, attitudes and beliefs (BenAkiva et al, 1999).…”
Section: Tence Could We Focus More On Patients and Use Appropriate Rmentioning
confidence: 99%